Timber-framed construction for multi-residential buildings class 2, 3, & 9c : design and construction guide for BCA compliant sound and fire-rated construction (Wood solutions ;, 2010)
"This technical manual is part of a suite of information, technical and training resources produced to support the use of wood in the design and construction of buildings."--T.p. verso.